Evaluation of Flap Shrinkage Using Magnetic Resonance Imaging Follow-up in the Treatment of Oral Cancer - Thoenissen, Philipp; Bucher, Andreas M.; Heselich, Anja; Sader, Robert; Vogl, Thomas; Ghanaati, Shahram (Journal of Reconstructive Microsurgery Open, 2023)
Objective Tumor resection and reconstruction in patients with oral squamous cell carcinoma often involves free flaps followed by radiation therapy. Volume loss of free flaps is common following transplantation and radiation therapy. Therefore, this study investigates the volume loss of free radial forearm flaps in the field of craniomaxillofacial surgery.Methods In a retrospective single-center clinical study, postsurgery magnetic resonance imaging (MRI) was analyzed in patients with a free radial forearm flap. Additional functional outcomes were observed. The size of transplants and volume shrinkage were measured over time. Additional functional outcomes were observed with a questionnaire at any follow-up. Transplant size and volume shrinkage were evaluated in 12 patients and showed a mean transplant volume loss in radial forearm free flaps of 33% within 100 weeks postsurgery.Results Depending on the site of transplantation, volume loss differed between the buccal region (38.33%), alveolar process (36.29%), and tongue (17.50%) and loss varied according to both radiation and chemotherapy (51.5%) or adjuvant radiotherapy (51.5%) compared with none of those (30%). Nine patients (75%) stated full functional satisfaction after this evaluation period.Conclusion MRI follow-up imaging is an adequate tool for measuring the volume shrinkage of free flaps. This study proves that overcorrection of flaps is necessary by expecting a loss of volume that depends on the site of transplantation and adjuvant therapy to reach a satisfying quality of life.
Keywords: MRI; free flap surgery; microsurgery